Comparison of Abdominal Muscle Thickness According to Duration after Side Body Crunch Exercise with Audiovisual Feedback - Won-Sik Bae, Keon-Cheol Lee, Dong-Yeop Lee, (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Background/Objectives: This study aims to show the transformation in the effect of side body crunches on abdominal muscle thickness through various types of feedback. Methods/Statistical analysis: 20 young, healthy adults (10 men and ten women) contributedto this study. The subjects were measured in a supine place. The dimension area of the internal oblique,transverse abdominis,and external oblique muscles was the right lower quadrant of the subjects, which is 2cm inward, alongside the anterior superior iliac spine. The width of abdominal muscles was measured by ultrasound measurement of the external oblique, internal oblique, and transverse abdominal muscles. Findings: The outcomes of this study were as follows.The prior homogeneity among the two groups was confirmed for the width of the abdominal muscle of the study subjects. The average values ​​of each powerwere taken for the 0th, 3rd, and 6th-week workouts. There was anessentialchangeamong the transverse abdominis, external oblique, and internal oblique muscles according to the period (p<.05), and there was no significant difference among the period and the group interaction effect and between the groups(p>.05). Improvements/Applications: Based on the present study’s findings, visual feedback applied during side body crunch exerciseswas influentialinchanging the width of the abdominal muscles.